2012
DOI: 10.1016/j.stem.2012.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Carm1 Regulates Pax7 Transcriptional Activity through MLL1/2 Recruitment during Asymmetric Satellite Stem Cell Divisions

Abstract: SUMMARY In skeletal muscle, asymmetrically dividing satellite stem cells give rise to committed satellite cells that transcribe the myogenic determination factor Myf5, a Pax7-target gene. We identified the arginine methyltransferase Carm1 as a Pax7 interacting protein and found that Carm1 specifically methylates multiple arginines in the N-terminus of Pax7. Methylated Pax7 directly binds the C-terminal cleavage forms of the trithorax proteins MLL1/2 resulting in the recruitment of the ASH2L:MLL1/2:WDR5:RBBP5 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
178
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(181 citation statements)
references
References 57 publications
3
178
0
Order By: Relevance
“…Intracellular signaling molecules such as peroxisome proliferator-activated receptor (PPAR)-γ coactivator-1α (PGC-1α), calcineurin (CN), p38 mitogen-activated protein kinase (p38), AMP-activated protein kinase (AMPK), silent mating type information regulator 2 homologue 1 (SIRT1), PPARβ and tumor suppressor protein p53 play a role in remodelling skeletal muscle toward a slower, more oxidative phenotype (16,18,19,20,21,22,23,24,25). In contrast, receptor interacting protein 140 (RIP140), E2F transcription factor 1 (E2F1), nuclear receptor corepressor 1 (NCoR1), and Baf60c have been shown to promote faster, more glycolytic characteristics (26,27,28,29,32). Thus, numerous molecules participate in the coordinated expression of morphological, biochemical and functional characteristics that define, and remodel, skeletal muscle phenotype (Fig.…”
Section: Skeletal Muscle Plasticitymentioning
confidence: 99%
“…Intracellular signaling molecules such as peroxisome proliferator-activated receptor (PPAR)-γ coactivator-1α (PGC-1α), calcineurin (CN), p38 mitogen-activated protein kinase (p38), AMP-activated protein kinase (AMPK), silent mating type information regulator 2 homologue 1 (SIRT1), PPARβ and tumor suppressor protein p53 play a role in remodelling skeletal muscle toward a slower, more oxidative phenotype (16,18,19,20,21,22,23,24,25). In contrast, receptor interacting protein 140 (RIP140), E2F transcription factor 1 (E2F1), nuclear receptor corepressor 1 (NCoR1), and Baf60c have been shown to promote faster, more glycolytic characteristics (26,27,28,29,32). Thus, numerous molecules participate in the coordinated expression of morphological, biochemical and functional characteristics that define, and remodel, skeletal muscle phenotype (Fig.…”
Section: Skeletal Muscle Plasticitymentioning
confidence: 99%
“…Prmt4 and Prmt5 have been implicated in promotion of myoblast differentiation through interaction with Mef2c or MyoD, respectively (36,37). Recent studies with muscle stem cell-specific knockout mouse models have suggested that Prmt4 and Prmt5 play critical roles in control of muscle stem cell functions during muscle regeneration (38,39). In this study, we characterized the role of Prmt7 in skeletal muscle metabolism by using Prmt7-deficient mouse models.…”
mentioning
confidence: 98%
“…However, SCs are still heterogenic, and among the distinct differentiation stages, the satellite stem cell population must be maintained to preserve their stemness, that is, long-term self-renewal and differentiation abilities. Accumulating data indicate that SCs maintain their population by asymmetric cell division [1][2][3][4] . The different differentiation stages of SCs are distinguishable by the expression of specific markers such as PAX7 and MYOD; PAX7 þ /MYOD À cells are quiescent, PAX7 þ /MYOD þ cells are activated and PAX7 À /MYOD þ cells are differentiating.…”
mentioning
confidence: 99%